New challenges in teaching EFL in agricultural institutions of Ukraine - Pantileienko, Kateryna; Пантілеєнко, Катерина Сергіївна (Дніпровський державний аграрно-економічний університет, 2022)
The paper defines and analyses the priorities in teaching EFL in agricultural education institutions in Ukraine. The most efficient ESP teaching approaches and techniques are discussed in the context of current priorities in higher education. Тhe question of Ukraine integration into the global higher education area and the necessity to be sensitive to the demands of modern employers and highly competitive labour market. Under the dynamic processes of globalisation and the integration of Ukraine into the world educational environment, making changes in the system of tertiary education has become of crucial necessity and priority. У статті визначено та проаналізовано пріоритети викладання англійської мови в аграрних навчальних закладах України. У контексті актуальних пріоритетів вищої освіти обговорюються найефективніші підходи та методики викладання англійської мови спеціального вжитку. Питання інтеграції України у світовий простір вищої освіти та необхідність бути чутливим до запитів сучасних роботодавців та високо конкурентного ринку праці. В умовах динамічних процесів глобалізації та інтеграції України у світове освітнє середовище відбуваються зміни в системі вищої освіти. освіта стала надзвичайною необхідністю та пріоритетом.
Нові виклики у викладанні англійської мови в аграрних закладах України
Keywords: students; студенти; methodology; методика; foreign language; іноземна мова; training; навчання